Der patentrechtliche Unterlassungsanspruch Historie, Reichweite und Reform - Plagge, Michael (Schriften zum geistigen Eigentum und zum Wettbewerbsrecht, 2022)
The question of possible limitations to injunctive relief under patent law has once again become the focus of public attention. The core of the discussion is whether the enforcement of injunctive relief in its current form can lead to unjustified hardship for infringers and third parties. As a result of the most recent debate, the German lawmaker added a proportionality defence in the 2nd PatModG. Against this backdrop, the author examines the current concept of injunctive relief in patent law, its history, scope and reform in order to develop a practice-oriented solution for resolving dysfunctional case constellations.